2006
DOI: 10.1158/1078-0432.ccr-06-0398
|View full text |Cite
|
Sign up to set email alerts
|

An Immunohistochemical Study of Morules in Endometrioid Lesions of the Female Genital Tract: CD10 Is a Characteristic Marker of Morular Metaplasia

Abstract: Purpose:To analyze immunohistochemically morules in endometrioid lesions to show that CD10 is a sensitive marker for morular metaplasia. Experimental Design: Immunohistochemical analysis of 53 instances of morular metaplasia comprising 1 cyclic endometrium and 52 endometrioid lesions associated with focal glandular complexity corresponding to 9 polyps, 4 atypical polypoid adenomyomas, 24 complex endometrial hyperplasias (18 with and 6 without atypia), 12 grade 1 endometrioid adenocarcinomas in early clinical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
54
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 22 publications
5
54
1
Order By: Relevance
“…The morular component of APA is strongly positive for CD10 as previously described in the literature [17], and this finding acts as an internal positive control for CD10 immunostaining. Strong CD10 immunoreactivity within the morular component with a complete lack of CD10 staining within the myofibromatous stromal component of the same specimen excludes a false-negative finding.…”
Section: Discussionsupporting
confidence: 74%
“…The morular component of APA is strongly positive for CD10 as previously described in the literature [17], and this finding acts as an internal positive control for CD10 immunostaining. Strong CD10 immunoreactivity within the morular component with a complete lack of CD10 staining within the myofibromatous stromal component of the same specimen excludes a false-negative finding.…”
Section: Discussionsupporting
confidence: 74%
“…Although ESM originates de novo from neoplastic glands, in a fifth of cases it coexists with morules (see below), where transitions between the distinct two types of metaplasia occur 1 23 53 58. This does not mean that neither all ESMs are necessarily neoplastic nor that all ESMs necessarily originate from morules.…”
Section: Epithelial Emcsmentioning
confidence: 99%
“…For these reasons, we think that caution should be applied in the interpretation of the article by Fujiwara et al [1] and in others [5] that reported TTF1 immunoreactivity in tumors other than those originating in the lung or thyroid and that used both antigen retrieval and/or avidin-biotin peroxidase complex methods. Chiarelli et al [3] have demonstrated that CD10 is a useful immunomarker of morules in endometrioid lesions of the female genital tract, and most recently, our group [4] evidenced that CD10 can also be useful in identifying morules in the BROCN-family tumors, all sharing alterations in the APC/β-catenin pathway. In fact, we believe the lesion depicted in Fig.…”
mentioning
confidence: 76%
“…The biotin is sometimes located in the nuclei, as can be seen in pregnancy-related endometria (Fig. 1A, B), in some morule-lacking adenocarcinomas of the gallbladder, in morules in cyclic endometrium and endometrial hyperplastic lesions [3], and in a group of tumors containing morules with cells displaying biotin-rich optically clear nuclei (BROCN; BROCN-family tumors), which includes endometrioid endometrial adenocarcinomas (Figs. 1C-E), ovarian endometrioid tumors, and others [4].…”
mentioning
confidence: 90%